FEATURES OF FORMATION OF REGIONAL CLUSTER STRUCTURES - Ekaterina V. Andreyeva (Статистика и экономика)
ARTICLE RETRACTEDIn article is considered features of formation of cluster structures for increase of efficiency of economic entities and growth of investment and innovative appeal of the region. Cluster structures are described as a specialized product oriented commands, which were created for common decision making about production, nancial and organizational questions.